Minx - Quinn, Julia, 1970-.; Copyright Paperback Collection (Library of Congress) (New York : Avon Books, 1996)
Rebelling against all societal conventions by wearing breeches and managing her elderly guardian's estate, feisty Henrietta Barrett is left at the mercy of distant cousin William Dunford when her guardian passes away.
Keywords: Fiction; Love stories